Community-Based Participatory Research Approach to Evidence-Based Research: Lessons From the Pacific Islander American Health Study - Panapasa, Sela (2012)
OBJECTIVES: Reports on the challenges and lessons learned from the Pacific Island American Health Study engagement with community-based organizations (CBOs) and faith-based organizations (FBOs) in Pacific Islander (PI) communities and mechanisms to facilitate the collection of robust data. METHODS: Academic–community partnership building was achieved with PI CBOs and FBOs. Focus group meetings were organized to plan various aspects of the study, develop questionnaire themes and protocols for survey, assist with the interviewer recruitment process, and strategize data dissemination plan. LESSONS LEARNED: The PIA-HS represents a model for overcoming challenges in data collection among small understudied populations. FBOs represent a valuable resource for community-based participatory research (CBPR) data collection and for effective interventions. CONCLUSION: The study methodology can be replicated for other racial/ethnic groups with high levels of religiosity combined with concentrated levels of residential clustering. Expansion of the Pacific Islander American Health Study (PIA-HS) to include other PI subgroups is encouraged.